Negosiasi Identitas Budaya Perantau Minangkabau Di Kota Bandung: Implementasi Filosofi “Di Mana Bumi Dipijak, Di Situ Langit Dijunjung” (Universitas Palangka Raya, 2026)
The objective of this research is to examine how Minangkabau migrants in Bandung negotiate their cultural identity and how the philosophy